1996
DOI: 10.1006/jmbi.1996.0273
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, Characterization and Properties of Plasmids Containing CGG Triplet Repeats from the FMR-1 Gene

Abstract: The FMR-1 gene for the human fragile-chi syndrome, a mental retardation disease inherited by non-Mendelian transmission, contains a genetically unstable CGG region in the 5' non-translated region. The severity of the disease is correlated with the length of the CGG tract. The cloning of 28 stable plasmids containing (CGG)n inserts (where n = 6 to 240) with different extents and types of sequence interruptions (polymorphisms), and in different orientations was accomplished by three strategies in Escherichia col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
110
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 81 publications
(123 citation statements)
references
References 39 publications
12
110
1
Order By: Relevance
“…Furthermore, no rearrangements were observed on analyzing individual colonies obtained from transforming the parental plasmids into E. coli HB101. Likewise, rearrangements were not observed previously in other prior instability studies with triplet repeat inserts in E. coli HB101 (10,16,18,19,39,86,(91)(92)(93). This confirms that the rearrangements were because of an intrinsic property of the pcDNA3.1 shuttle vector that carries the SV40 origin of replication.…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…Furthermore, no rearrangements were observed on analyzing individual colonies obtained from transforming the parental plasmids into E. coli HB101. Likewise, rearrangements were not observed previously in other prior instability studies with triplet repeat inserts in E. coli HB101 (10,16,18,19,39,86,(91)(92)(93). This confirms that the rearrangements were because of an intrinsic property of the pcDNA3.1 shuttle vector that carries the SV40 origin of replication.…”
Section: Resultssupporting
confidence: 86%
“…Previous studies showed a marked effect of orientation of trinucleotide repeats (CTG⅐CAG, CGG⅐CCG, and GAA⅐TTC) with respect to the origin of replication (10,16,18,19,21,39,85,86). Therefore, we studied plasmids carrying the (CCTG⅐CAGG) repeats in both orientations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, the extent of instability for a (CTG) n or (CGG) n tract depends on its length and orientation relative to the origin of replication in Escherichia coli (30,31). We propose that high levels of supercoiling (writhe) accumulate within the TRS during processes such as transcription and replication, which lead to instability.…”
Section: Discussionmentioning
confidence: 98%